2020
DOI: 10.1007/s12015-020-10076-9
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-Specific-Processing Protease 7 Regulates Female Germline Stem Cell Self-Renewal Through DNA Methylation

Abstract: Ubiquitin-specific-processing protease 7 (Usp7) is a key deubiquitinase controlling epigenetic modification and regulating the self-renewal, proliferation, and differentiation of stem cells. However, the functions and mechanisms of action of Usp7 on female germline stem cells (FGSCs) are unknown. Here, we demonstrated that Usp7 regulated FGSC self-renewal via DNA methylation. The results of Cell Counting Kit-8 and 5-ethynyl-20-deoxyuridine assays showed that the viability and proliferation of FGSCs were negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Our previous study found that DNA methylation is involved in the unipotency of FGSCs and maintains their sexual identity 12 . Zhao et al showed that Usp7 regulates the self-renewal and differentiation of FGSCs through DNA methylation 13 . In addition, long noncoding RNA 14 , 15 , Circular RNA 16 , and m6A modification 17 have been reported to participate in the epigenetic regulation of FGSCs development.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study found that DNA methylation is involved in the unipotency of FGSCs and maintains their sexual identity 12 . Zhao et al showed that Usp7 regulates the self-renewal and differentiation of FGSCs through DNA methylation 13 . In addition, long noncoding RNA 14 , 15 , Circular RNA 16 , and m6A modification 17 have been reported to participate in the epigenetic regulation of FGSCs development.…”
Section: Introductionmentioning
confidence: 99%